Formulasi Krim Bibir dengan Ekstrak Antosianin dari Bunga Telang (Clitoria ternatea) sebagai Pewarna Alami - Aprilia, Jelita; Rahmalia, Winda; Budi, Firman Shantya (Jurnal Ilmiah Farmasi, 2025)
Background: Butterfly pea (Clitoria ternatea) is a tropical plant rich in anthocyanins, particularly from the flavonoid group, which has potential as a natural dye and antioxidant in cosmetic formulations.Objective: This study aims to investigate the phytochemical characteristics of anthocyanin extract from butterfly pea flowers and the physical and chemical stability of lip cream formulated with the extract.Method: Anthocyanin extract from butterfly pea flowers was formulated into a lip cream base at concentrations of 0, 2, 4, and 6%, followed by a physical stability test conducted over a period of one month on days 0, 7, 14, 21, and 28. The results were then compared with established standards.Results: The anthocyanin extract of butterfly pea flower contains flavonoids, saponins, tannins, and terpenoids. Four lip cream formulations prepared with varying concentrations of the extract exhibited a thick texture, a grape-like aroma, and colors ranging from ivory to purple. The formulations had viscosities between 5,500 and 13,000 cP, adhesion times ranging from 7.10 to 26.8 seconds, and spreadability values between 5 and 7.5 cm.Conclusion: All stability tests of the butterfly pea flower extract lip cream formulations met the required criteria, except for the homogeneity test. Formulation 1 (2%) was identified as the most optimal. All stability tests for the butterfly pea flower extract lip cream formulations met the required criteria, except for the homogeneity test. Formulation 1 was identified as the most optimal, containing 2% extract concentration.